Sceptic: pseudotime analysis for time-series single-cell sequencing and imaging data - Gang Li; Hyeon-Jin Kim; Sriram Pendyala; Ran Zhang; Jean-Philippe Vert; Christine M. Disteche; Xinxian Deng; Douglas M. Fowler; William Stafford Noble (Genome Biology)
Abstract Several computational methods have been developed to construct single-cell pseudotime embeddings for extracting the temporal order of transcriptional cell states from time-series scRNA-seq datasets. However, existing methods suffer from low predictive accuracy, and this problem becomes even worse when we try to generalize to other data types such as scATAC-seq or microscopy images. To address this problem, we propose Sceptic, a support vector machine model for supervised pseudotime analysis. We demonstrate that Sceptic achieves significantly improved prediction power relative to state-of-the-art methods, and that Sceptic can be applied to a variety of single-cell data types, including single-nucleus image data.